A preliminary study on antioxidant activities of saffron petal extracts in lambs (Veterinary Science Development, 2014)
This study assessed the effects of hydroalcoholic extract of saffron (Crocus sativus L) petals on male lambs and was aimed at evaluating the antioxidant activity of this extract during a 15-day period. Fourteen male lambs were divided randomly into three treatment groups (n=4 each) and a control group (normal saline; n=2). Saffron petal extract at 500, 1000 and 1500 mg/kg was administered by gavage once daily on days 1 and 3 of the experiment for treatment groups. Blood samples were obtained on days 6 and 14 of the study. Serum and plasma were stored at −21°C for further analysis. Heart rate, respiratory rate, rectal temperatures and body weight of each lamb were recorded in the distinctive intervals from day 0 to the last day of the study. Total antioxidant capacity levels were increased significantly with any dose of the extract on the first day of sampling. There was no statistical difference in the levels of malondialdehyde and total thiol between the treatment and the control group son the 6th and the 14th days of the experiment. Also, no significant differences were identified in the concentrations of glucose, blood urea nitrogen, creatinine, uric acid, total cholesterol, triglyceride, albumin, globulin, total protein, aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, gamma glutamyle transferase, total bilirubin, direct and indirect bilirubin between control and treatment groups in male lambs during this study. Recorded vital signs and body weight in control and treatment groups showed no significant differences. The present results suggest that the hydroalcoholic extract of saffron petals has antioxidant activity in sheep.